Navigating to the most promising directions amid complex fields of vaccine development: a chlamydial case study. (2nd December 2019) - Lizárraga, David; Carver, Scott; Timms, Peter
ABSTRACT: Background : Vaccine-development research is proliferating making it difficult to determine the most promising vaccine candidates. Exemplary of this problem is vaccine development against Chlamydia, a pathogen of global public health and financial importance. Methods : We systematically extracted data from studies that included chlamydial load or host immune parameter measurements, estimating 4, 453 standardized effect sizes between control and chlamydial immunization experimental groups. Results : Chlamydial immunization studies most often used (78%) laboratory mouse models. Depending on chlamydial species, single and multiple recombinant protein, viral and bacterial vectors, dendritic transfer, and dead whole pathogen were most effective at reducing chlamydial load. Immunization-driven decrease in chlamydial load was associated with increases in IFNg, IgA, IgG1, and IgG2a. Using data from individual studies, the magnitude of IgA and IgG2a increase was correlated with chlamydial load reduction. IFNg also showed this pattern for C. trachomatis, but not for C. muridarum . We also reveal the chlamydial vaccine development field to be highly bias toward studies showing these effects, limiting lessons learned from negative results. Conclusions : Most murine immunizations against Chlamydia reduced chlamydial load and increased host immune parameters. These methods are novel for vaccine development and are critical in identifying trends where large quantities of literature exist.